Exploring Service Accessibility and Quality for Differently-Abled Students: A Qualitative Analysis at a South African University of Technology - Naidoo, Agendri; Adam, Jamila Khatoon; Akpa-Inyang, Francis (Research in Social Sciences and Technology, 2024)
This qualitative study investigates the service experiences of differently-abled students within the Financial Aid Department of a prominent South African University of Technology. Employing a semi-structured interview schedule aligned with the Service Quality model (SERVQUAL), five dimensions—tangibles, assurance, empathy, reliability, and responsiveness—are explored. The study unveils the significant challenges students face, including issues related to the location and accessibility of the department, staff approachability, and the reliability of communication systems. The discussion section draws on relevant literature to synthesise the findings, providing comprehensive insights into the intricacies of service delivery for differently-abled students. The study concludes with actionable recommendations for enhancing service quality and inclusivity, addressing the unique needs of this student demographic in the evolving landscape of South African higher education.